ICT and Substitution between Out-of-home and At-home Work; the Importance of Timing - Thomas de Graaff; Piet Rietveld (Tinbergen Institute, 2003)
This paper investigates the determinants of at home and out-of-home labor supply in the Netherlands in the 199s, focusing on the presence of ICT technologies in households -in particular modempossession.To investigate these determinants, a sequential hurdle model is estimated where people first decideto work and then decide to divide total labor supply in at home and out-of-home labor supply. Tocorrect for possible endogeneity, the modem variable is estimated with use of instrumental variables.When we only consider office hours, possession of ICT facilities at home stimulates both at homeand out-of-home labor supply. Thus, the two may be called complements from the ICT perspective.However, outside office hours, modem possession leads to less work out-of-home. During this part ofthe day the time worked less on the job is partly substituted by work at home. Thus, during thispart of the week we find that substitution dominates. However, since labor supply during office hoursdominates labor supply during the rest of the week we find complementarity as the main feature ofoverall labor supply. These results underline the importance of timing issues.
Keywords: J22; 330; Bivariate tobit; Labor supply; Modem possession; Netherlands; At home labor supply; Out-of-home labor supply; Teleworking.; Telearbeit; Telekommunikation; Informationstechnik; Arbeitsangebot; Niederlande